Simultaneous Changes in Astigmatism with Noncycloplegia Refraction and Ocular Biometry in Chinese Primary Schoolchildren - Yaoyao Lin; Dandan Jiang; Chunchun Li; Xiao Chang; Balamurali Vasudevan; Xiaoqiong Huang; Wenzhe Zhou; Lei Qin; Yanyan Chen (Journal of Ophthalmology)
Purpose. To assess the changing profile of astigmatism in Chinese schoolchildren and the association between astigmatism changes and ocular biometry. Methods. We examined and followed up 1,463 children aged 6–9 years from Wenzhou, China. We measured noncycloplegic refraction twice each year and tested axial length (AL) and corneal radius of curvature (CRC) annually for two years. We defined clinically significant astigmatism (CSA) as ≤−0.75 diopter (D) and non-CSA astigmatism as ≤0 to >−0.75 D. Results. Prevalence of CSA at baseline was 22.4% (n = 327) and decreased to 20.3% (n = 297) at the two-year follow-up (P=0.046). Ninety-two (8.1%) non-CSA children developed CSA. In multiple regression, after adjusting for age, gender, baseline cylinder refraction, and axis, children who had longer baseline ALs (>23.58 mm; odds ratio (OR) = 5.19, 95% confidence interval (CI): 2.72–9.90) and longer baseline AL/CRC ratio (>2.99, OR = 4.99, 95% CI: 2.37–10.51) were more likely to develop CSA after two years. Four-hundred and two (27.5%) children had increased astigmatism, 783 (53.5%) had decreased, and 278 (19.0%) had no change during the two-year follow-up. Children with increased astigmatism had longer baseline ALs (23.33 mm, P<0.001), higher AL/CRC ratios (2.99 mm, P<0.001), and more negative spherical equivalent refraction (SER) (−0.63 D, P<0.001) compared with the decreased and no astigmatism change subgroups. Also, children in the increased astigmatism subgroup had more AL growth (0.68 mm, P<0.001), higher increases in AL/CRC ratio (0.08, P<0.001), and more negative SER change (−0.86 D, P<0.001) compared with the decreased and no astigmatism change subgroups. Conclusions. The prevalence of astigmatism decreased slightly over the two-year study period. Longer ALs and higher AL/CRC ratios were independent risk factors for developing CSA. Increased astigmatism was associated with AL growth, AL/CRC ratio increases, and the development of myopia. This trial is registered with ChiCTR1800019915.